EVALUASI SISTEM TATA KELOLA PROGRAM QUR’AN DI PONDOK PESANTREN MASKANUL HUFFAZ - Irwansyah, Saripudin; Muthi, Ibnu (Jurnal Kinerja, 2025)
This study aims to evaluate the governance system of the Qur'an program at Pondok Pesantren Maskanul Huffaz, one of its flagship programs that plays a strategic role in producing high-quality Qur'an memorizers. The evaluation was conducted using the CIPP model (Context, Input, Process, Product) to provide a comprehensive overview of the program's effectiveness from planning, implementation, to the outcomes achieved. This research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The findings indicate that the Qur'an program's governance system has been implemented systematically, supported by a solid managerial structure and special institutional attention. However, challenges remain, particularly regarding some instructors’ limited understanding and application of the established system, as well as the participants’ punctuality in attending learning sessions. Approximately 70% of the students have successfully completed the memorization of 30 juz with high-quality recitation based on fluency, articulation (makhārij al-ḥurūf), lengthening (mad), and tajwīd accuracy. The alignment between the financial resources utilized and the outcomes achieved demonstrates a high level of efficiency and productivity. The program’s excellence is further evident in its integration of character education and Islamic insight into the learning system.